COMPARATIVE STUDY OF DEVELOPMENTAL AND REPRODUCTIVE CHARACTERISTICS OF CHRYSOPERLA CARNEA (S TEPHENS) (NE UROPTERA: CHRYSOPIDAE) AT DIFFERENT REARING TEMPERATURES - S. Nadeem; M. Hamed; M. K. Nadeem; M. Hasnain; B. M. Atta; N. A. Saeed; M. Ashfaq (Journal of Animal and Plant Sciences, 2012)
Role of temperature is very critical for the development and reproduction of insects like predator, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae). Present study was ascertained under laboratory conditions in a completely randomized design to sort out the comparatively effective rearing temperature by studying developmental and reproductive parameters at different temperatures conditions. Results showed that rearing at the different tested temperatures 20, 25, 28, 31, 35 and 40oC, the developmental and reproductive characteristics of C. carnea observed quite suitable at 28oC which proved to be the best among the other tested rearing temperatures. Rearing at 31 and 35oC had little effect on both the parameters of insect under study. It was inferred from present findings that rapid development of C. carnea observed at 31oC, which can gave useful rearing when quick development desired in laboratories. At 25oC, the reproduction rate of adult was the highest, as females tends to oviposit 10 days after emergence with 9 eggs per day and a total of 179.3 eggs per female. While over all better developmental and reproductive traits were recorded at 28oC. Slow and prolonged development was observed at 20oC, while no development recorded at high temperature of 40oC. Hence, it is demonstrate from the present study that the developmental and reproductive traits of C. carnea are directly dependent upon prevailing temperature of the environment.
Keywords: Low temperature; rearing; Chrysoperla carnea